Single versus double burr holes craniostomy drainage for chronic subdural hematoma: A systematic review and meta-analysis of randomized clinical trials - Abdulaziz M. Alghamdi; Abdulrahman Ahmad Takroni; Abdulwhab M. Alotaibi; Razan Ayed Alboqami; Orjwan Hashem Ateeq; Fares F. Alsayegh; Faisal Alotaibi (World Neurosurgery: X, 2025)
Objective: This systematic review and meta-analysis aimed to compare the efficacy and safety of single- and double-burr hole craniostomies (sBHC) and (dBHC) in the management of chronic subdural hematoma (cSDH). Methods: The PubMed, MEDLINE, Embase, and Cochrane CENTRAL databases were systematically searched for relevant articles. The included articles were randomized controlled trials (RCTs) written in English that compared the efficacy or safety of sBHC to that of dBHC for the treatment of patients with cSDH. Results: Nine RCTs were included in this systematic review. The length of surgery was significantly shorter in the sBHC group (mean difference = −20.65, 95 % CI [-28.58, −12.72], p < 0.00001, I2 = 96 %). The mean length of surgery in sBHC was 34.9 min, compared to 55.5 min for a dBHC. There was no significant difference in the postoperative Glasgow Coma Scale (GCS) between the groups, presence of postoperative infections, presence of postoperative pneumocephalus, length of hospital stay, recurrence rates, and mortality rate. Conclusion: Both sBHC and dBHC are efficacious surgical techniques for managing cSDH. Based on this meta-analysis of RCTs, the safety and efficacy of sBHC and dBHC were comparable without statistically significant differences.